2021
DOI: 10.3390/ijerph18189836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rare Earth Elements on Blood Pressure and Their Exposure Biomarkers: Evidence from Animal Experiments

Abstract: Solid fuel combustion is an important source of the release of rare earth elements (REEs) into the ambient environment, resulting in potential adverse effects on human cardiovascular health. Our study aimed to identify reliable exposure biomarkers of REE intake and their potential role in blood pressure change. A total of 24 rats were administered with 14 REE chlorides at four doses (six rats per group). Fur samples were collected both before and after administration. Blood samples were collected after 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Among the published papers in the first edition, the drivers of energy choices, the emission characteristics of solid fuel combustion, spatial and temporal variations in air pollution at different scales, and the health effects of the particle composition of solid fuel combustion were systematically discussed [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Mperejekumana et al revealed that higher socio-economic levels (credit access) could increase the likelihood of choosing LPG by 22.7%, while higher levels of education can also help residents to choose cleaner residential fuels [ 1 ].…”
mentioning
confidence: 99%
“…Among the published papers in the first edition, the drivers of energy choices, the emission characteristics of solid fuel combustion, spatial and temporal variations in air pollution at different scales, and the health effects of the particle composition of solid fuel combustion were systematically discussed [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Mperejekumana et al revealed that higher socio-economic levels (credit access) could increase the likelihood of choosing LPG by 22.7%, while higher levels of education can also help residents to choose cleaner residential fuels [ 1 ].…”
mentioning
confidence: 99%